The Importance of Improving Employee Performance through Optimizing Job Training, Work Motivation and Work Ethic: A Literature Review - Hartadi, Agung; Sujoko, Sujoko (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2025)
This study examines the influence of job training, work motivation, and work ethic on employee performance by reviewing articles from 2019 to 2024. The analysis focuses on methodological approaches, empirical findings, and theoretical implications to understand how these factors impact performance. Job training plays a crucial role in developing human resources by enhancing employee skills and aligning them with organizational needs. Tailored training programs address individual differences in skills and motivations, helping employees understand their roles better. Work motivation is essential for driving employees to achieve organizational goals. Similarly, a strong work ethic fosters dedication and enthusiasm, reflecting positively on both individual and organizational success. Establishing a work culture that promotes excellence is critical for sustained performance improvement. The findings of this study are expected to guide practitioners and policymakers in designing effective human resource development programs. Through a comprehensive literature review, alternative research problems, innovative topic ideas, and opportunities for further exploration are identified. This approach emphasizes the importance of integrating technical skills with mindset, attitude, and psychological motivation, highlighting a holistic strategy for enhancing employee performance in dynamic work environments.